Exploring Financial Distress Determinants in Indonesia’s Property and Real Estate Sector - Utami, Fransita Karmelita Budi; Tyas Danarti Hascaryani (Journal of Development Economic and Social Studies, 2025)
The property and real estate sector in Indonesia is highly capital-intensive and vulnerable to financial instability, making the early identification of financial distress crucial for corporate sustainability. This study aims to analyze the effect of profitability (ROA), liquidity (CR), leverage (DER), free cash flow (FCF), and firm size (Total Assets) on the level of financial distress in property and real estate companies listed on the Indonesia Stock Exchange during the 2018–2024 period. The research employs a quantitative approach using panel data regression with the Random Effect Model (REM) and robust standard errors, based on a sample of 17 companies over seven years. The analysis uses a modified Z-Score formula as an indicator of financial distress. The findings reveal that CR and FCF have a positive and significant effect on the Z-Score, indicating stronger financial resilience, while DER and firm size significantly reduce the Z-Score, suggesting a higher risk of financial distress. ROA does not show a statistically significant influence. These results highlight the critical role of liquidity and free cash flow in maintaining financial health, while excessive leverage and scale can amplify financial risk. The study implies that firms must strengthen their asset management and capital structure to mitigate distress and enhance long-term viability.